Lateralized Changes in Language Associated Auditory and Somatosensory Cortices in Autism - Deemyad, Tara (Frontiers in Systems Neuroscience, 2022)
Lateralized specialization of the two cerebral hemispheres is a fundamental structural hallmark of the human brain and underlies many cognitive functions and behavioral abilities. In typical developing individuals the influence of handedness on performance of various sensory modalities and the cortical processing has been well recognized. Increasing evidence suggests that several neurodevelopmental and psychiatric disorders such as bipolar disorder, schizophrenia, and autism spectrum disorders (ASD) are associated with abnormal patterns of cerebral lateralization. Individuals with ASD exhibit abnormal structural and functional lateralization of circuits subserving motor, auditory, somatosensory, visual face processing, and language-related functions. Furthermore, a high prevalence of atypical handedness has been reported in ASD individuals. While the hemispheric dominance is also related to functions other than handedness, there is a clear relationship between handedness and language-related cortical dominance. This minireview summarizes these recent findings on asymmetry in somatosensory and auditory cortical structures associated with language processing in ASD. I will also discuss the importance of cortical dominance and interhemispheric disruption of balance between excitatory and inhibitory synapses as pathophysiological mechanisms in ASD.